Sistem Informasi Koperasi Simpan Pinjam Berbasis Web (Studi Kasus : Koperasi Unit Desa Sawah Sudut Selayo) - Suci Wulandari; Edni Wulandari; Edwin Anwar (Ikatan Ahli Informatika Indonesia, 2020)
Village unit cooperatives are cooperatives in rural areas which are engaged in providing community needs related to community activities themselves. Village unit cooperatives can also be called multi-business cooperatives because they try to fulfill various fields such as savings and loans, consumption, production, marketing and services. KUD Saving and Credit Cooperative Sawah Sudut Selayo, all data processing is still using a manual system. So that data processing can be done quickly and accurately, we need a system that can help solve problems that arise due to the use of the old system. Therefore a Web-Based Savings and Loans Information System was built using the PHP programming language and the MySQL Database, with the proposed savings and loan information system, expected to be able to produce more accurate member data and member deposits, making it easier to input member data and amounts member deposits.